SKRINING AKTIVITAS ANTIBAKTERI DAUN KELOR (Moringa oleifera), DAUN BIDARA LAUT (Strychnos ligustrina Blume), DAN AMOXICILIN TERHADAP BAKTERI PATOGEN Staphylococcus aureus - Edi Suriaman (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2017)
Exploration of a variety of plants as a source of antibacterial has been done, but it is not all plants effective to inhibit the growth of bacteria. This study aims to determine the difference between the ability of the antibacterial activity of plant leaves Moringa oleifera and Strychnos ligustrina Blume against Staphylococcus aureus bacteria growth. This research is an experiment with a completely randomized factorial design (CRD) 3x4 with four replicates. The materials use is ethanol extract of the leaves of Moringa leaf extract, S. ligustrina, and amoxicillin. Testing the antibacterial activity performed on Mueller-Hinton agar media with the diffusion method. The analysis and interpretation of results were done by ANOVA 95% (α: 0.05). Susceptibility bacteria to antibiotics, and plant extracts assessed according to standard NCCLS (National Committee for Clinical Laboratory Standards). The antibacterial agent (ethanol extract of Moringa leaf, ethanol extract of S. ligustrina leaf, and amoxicillin) and concentrations influence significantly inhibit the growth of S. aureus bacteria. S. aureus bacteria are sensitive only at 100% concentration with inhibition zone diameter 21.5 ± 5:35 mm, when given the leaf extract of S. ligustrina, and at a concentration of 75% with a diameter of 14.3 ± 1.32 mm is intermediate. The bacteria behave-resistant to the compound of M. oleifera leaf extract and amoxicillin at all concentrations. Diameter of zones of inhibition amoxicillin equal 9.99 ± 2.02 mm with 100% concentration treatment. While the treatment of M. oleifera leaf extract, at a concentration of 75% and 100%, resulting in the largest inhibition zone each is 3.9 ± 0.64 and 3.82±0.57 mm.